Rethinking library resource sharing: new models for collaboration. Issue 1 (11th February 2014) - Bailey-Hainer, Brenda; Beaubien, Anne; Posner, Beth; Simpson, Evan
Abstract : Purpose: – The purpose of this paper is to highlight significant changes in the information discovery landscape; discuss evolution in discovery systems and their connection to resource sharing; discuss the use of best practices by resource sharing practitioners; and describe new collaborations among libraries that change the definition of resource sharing. Design/methodology/approach: – The authors observed the library landscape with a focus on discovery systems, interlending systems, and collaborative resource sharing models and reviewed literature related to these areas to structure discussion and draw conclusions about the changing role and definition of resource sharing. Findings: – Innovations in discovery have significant impact on library resource sharing. Resource sharing practitioners are using best practices to improve services and develop new roles. New models for collaboration are changing the definition of library resource sharing. Originality/value: – This paper positions resource sharing as a dynamic, highly strategic area of service with growing importance to twenty-first century libraries and challenges readers to consider what new partnerships and collaborative models will benefit both libraries and their communities.